The Impact of Health Consciousness and Environmental Awareness on Sports Enthusiasts’ Purchase Intentions for Sustainable Sports Products - Youyou Li; Ningning An (World)
(1) Background: With the growing severity of global environmental issues and increasing consumer health consciousness, green consumption has become a prominent focus in both research and practice. However, studies on the mechanisms of health consciousness and environmental awareness influencing the purchase intentions of sports enthusiasts toward sustainable sports products remain relatively limited. This study investigates how health consciousness and environmental awareness impact the green consumption behavior of sports enthusiasts through psychological pathways, including attitude, subjective norm, and perceived behavioral control, aiming to reveal their underlying mechanisms. (2) Methods: Based on the extended Theory of Planned Behavior (TPB), this study developed a theoretical model incorporating health consciousness and environmental awareness. Data were collected via a questionnaire survey, yielding 407 valid responses. The sample was gender-balanced (52.8% male, 47.2% female), predominantly consisting of young individuals aged 26–35 (44.7%) and 18–25 (28.0%), with primary occupations being company employees/managers (46.2%) and students/teachers (25.3%). The collected data were analyzed using SPSS and AMOS software to systematically evaluate the research hypotheses and the model’s applicability. (3) Results: The model exhibited excellent fit indices, with a χ2/df value of 2.129, an RMSEA value of 0.053, an RMR value of 0.029, and GFI, CFI, NFI, and NNFI values all exceeding 0.90, indicating that the model structure adequately explained the relationships among latent variables. All research hypotheses were significantly supported (p < 0.01), demonstrating that health consciousness and environmental awareness not only directly influence purchase intentions but also exert significant indirect effects through attitude, subjective norm, and perceived behavioral control. (4) Conclusions: Health consciousness and environmental awareness are critical drivers of sports enthusiasts’ purchasing behavior for sustainable sports products. This study deepens the understanding of the mechanisms underlying green consumption behavior and offers practical implications for related businesses. Companies should enhance product healthiness and environmental friendliness while optimizing consumer psychological perceptions to increase purchase intentions.